THE IMPACT OF URBANIZATION ON EDUCATIONAL LANDUSE IN SULEJA, NIGER STATE, NIGERIA - Adamu Abubakar, Adamu Bala, Shidali Samuel David, Habib Abdullahi, Yisa Moses Kodan5 (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
Urbanization has impacts on social change and modernization which are parts of a continuum rather than empirically separate issues. Suleja has been surrounded by growing settlements whose influence constantly threatens the infrastructural facilities. There has been difficulty monitoring the extent and rapidity of the changes occurring within the area. The research aimed to assess the changes in educational land use in Suleja between 2009 and 2019 and also to identify the magnitude of the change. 375 questionnaires were administered in a proportion of intervals of houses based on the arrangement in the study area to acquire the socio-economic characteristics of the area. Population data was also used to analyze growth pattern(s) in the area and a field survey was carried to ascertain the numbers of schools in the study area. It was discovered that 4708sqm of land was used for educational purposes as of 2000 and there was an increase to 8552sqm as of 2012 and 127431.8sqm in 2019. The study also noted that the majority of schools within the residential areas are privately owned. It also noted that the majority of private own schools were within the residential areas. It was therefore recommended that a New Master Plan for Suleja should be developed because the only available one was developed in 1986.